Clinical and pathological features of metastatic adenocarcinoma of the prostate to the ileum - Ecke, Thorsten H. (Cent European J Urol, 2014)
We present a case of a 74-year-old white male with a history of prostate cancer with unusual metastasis to the ileum, and with ileus as a very unusual first symptom of prostate cancer. This patient presented to us with histologically confirmed metastasis of the ileum after resection in the Department of Surgery.